Safety evaluation of the food enzyme catalase from the non‐genetically modified Aspergillus tubingensis strain AE‐CN - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract The food enzyme catalase (hydrogen‐peroxide:hydrogen‐peroxide oxidoreductase; EC 1.11.1.6) is produced with the non‐genetically modified Aspergillus tubingensis strain AE‐CN by Amano Enzyme Inc. The absence of viable cells of the production organism in the food enzyme was not demonstrated. The food enzyme is intended to be used in five food manufacturing processes: production of baked products, processing of egg and egg products, production of fruit and vegetable products other than juices, production of cheese and production of fish roes. The dietary exposure to the food enzyme total organic solids (TOS) was estimated to be up to 0.325 mg TOS/kg body weight (bw) per day in European populations. The results of the in vitro genotoxicity studies indicated the presence of a clastogenic agent in the food enzyme which could not be dismissed due to limitations in the in vivo studies. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 323 mg TOS/kg bw per day, the highest dose tested. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and one match was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, but the likelihood is low. Because of the results of the genotoxicity studies, and as the absence of viable cells from the production strain was not demonstrated, the Panel was unable to establish the safety of the food enzyme.